SOLITARY FIBROUS TUMOR OF THE BRAIN: A CASE REPORT: TUMOR FIBROSO SOLITARIO CEREBRAL: A PROPÓSITO DE UN CASO - Ortiz Ramos, Valeria Antuanne (2024)
Introduction: Solitary fibrous tumors (SFTs) are rare mesenchymal neoplasms that, although typically develop in the visceral pleura, occasionally occur in the intracranial cavity. Furthermore, they are characterized by high rates of metastasis and recurrence.Case Report: We present the case of a 59-year-old male patient with a 3-month history of headache and bradyphrenia. Computed tomography revealed a neoformative tumor infiltrating the nasal cavity, ethmoid sinuses, and anterior cranial fossa, involving the left frontal lobe. The patient underwent two exploratory craniectomies, during which diagnoses suggestive of high-grade glial neoplasia and SFT were made. For precise diagnosis, immunohistochemistry was performed, which was consistent with solitary fibrous tumor. The case is analyzed, focusing particularly on histopathological aspects, the unusual location of this tumor, and its variable clinical manifestations.